2013
DOI: 10.1371/journal.pone.0076961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taurine Supplementation on Hepatic Markers of Inflammation and Lipid Metabolism in Mothers and Offspring in the Setting of Maternal Obesity

Abstract: Maternal obesity is associated with obesity and metabolic disorders in offspring. However, intervention strategies to reverse or ameliorate the effects of maternal obesity on offspring health are limited. Following maternal undernutrition, taurine supplementation can improve outcomes in offspring, possibly via effects on glucose homeostasis and insulin secretion. The effects of taurine in mediating inflammatory processes as a protective mechanism has not been investigated. Further, the efficacy of taurine supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 69 publications
5
61
1
Order By: Relevance
“…These beneficial effects on glucose metabolism persist into adult life [23]. We have also shown recently that maternal taurine supplementation can modify maternal and offspring markers related to hepatic inflammation and lipid metabolism in the setting of maternal obesity [24].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…These beneficial effects on glucose metabolism persist into adult life [23]. We have also shown recently that maternal taurine supplementation can modify maternal and offspring markers related to hepatic inflammation and lipid metabolism in the setting of maternal obesity [24].…”
Section: Introductionmentioning
confidence: 82%
“…Details on the protocol utilized for fructose and taurine supplementation have been published previously by our group [8,24]. Virgin Wistar rats were time mated at 100 days of age using an estrous cycle monitor (EC-40; Fine Science Tools, San Francisco, USA, USA), and mating was confirmed by the presence of spermatozoa following a vaginal lavage.…”
Section: Animal Modelmentioning
confidence: 99%
“…Solon et al (2012) reported that intracerebroventricular administration of Tau increased JAK2/STAT3 pathway activation. This amino acid also shows anti-inflammatory properties by decreasing cytokine levels in the brain and peripheral tissues (Lin et al 2013;Li et al 2013;Su et al 2014). In addition, hypothalamic pAkt/ Akt protein content was higher in CHT mice (Camargo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of maternal diet-induced obesity in animal models has been reviewed elsewhere (42) and will only be briefly reviewed here. In rodents, maternal HF diet during pregnancy and lactation induces obesity and hepatic steatosis in the offspring, irrespective of postnatal diet (43) and induces insulin and leptin resistance (44), hypertension (45), and hepatic inflammation in offspring (46). Sex-specific obesity risk and metabolic dysfunction have also been shown and have become a focus for some studies (47).…”
Section: Overview Of Experimental Studies On Outcomes After Maternal mentioning
confidence: 99%